Instagram as a branding tool for responsible dog food - Galdós-Tangüis, Isabella (2024)
Dog owners feel a commitment to give their pets a healthy life. Due to this trend, new food products have been created. Advertising has changed, as well as the elements that make up branding. In order to understand the construction of branding, this study analyzed the responsible food brand Barker and the elements that compose it. Its approach is qualitative. Fifteen customers were interviewed. A guide of questions grouped into 4 categories was constructed: branding, brand value, communication and Instagram. It was found that the brand conveys a value of responsibility for the feeding of animals with a branding that revolves around this theme. The interviewees perceive the branding as a communication close to their customers, which transmits transparency and concern for pets.